THE IMPLEMENTATION OF KALOSARA CUSTOM IN MEDIATING MEDICAL DISPUTES - Akib, Ma'ruf; Ichlas, Rudy Iskandar (Jurnal Pembaharuan Hukum, 2023)
This study aims to determine and analyze the constitutionality of Kalosara custom in mediating disputes between doctors and patients in Konawe Regency. The method in this research uses a sociological juridical approach. The results of this study are The role of the Kalosara as customary law has a broad scope as a legal sub-system in society, as the Kalosara is known to prioritize unity and peace through mediation by means of deliberation and consensus. The Sara Medulu procession carried out by doctors from Konawe Hospital came to the victim with the intermediary of a Tolea as a form of seriousness to settle by custom. Customary settlement with a family atmosphere makes both parties feel defeated by each other. This condition is far more beneficial than legal settlement through the litigation process where there are parties who are won and defeated.